Prevocalic word-initial glottal stops in Rote: Implications to language revitalisation - Tamelan, Thersia Magdalena (Masyarakat Linguistik Indonesia, 2024)
This paper presents an analysis of word-initial glottal stops in Rote and its implications for language revitalization programs. A number of phonological, morphological and syntactic evidence confirms that, in most cases, the status of the initial glottal stops can be determined; some are epenthetic, while others are contrastive. The difference between the two is evident in specific environments. Only a few instances are found in which the data are ambiguous. The data from Rote shows that a unitary analysis of the word-initial glottal stops is not possible. Thus, the status of such glottal stops needs to be carefully considered in orthography design for Rote languages to avoid underrepresentation or overrepresentation, which may lead to issues in the learnability of the orthography. This study contributes to (i) the exploration of variation and universality of prevocalic initial glottal stops, especially in Eastern Indonesian languages, and (ii) the orthography development of languages in Rote and the neighboring languages as an effort to language revitalization.